CD36-fatty acid-mediated metastasis via the bidirectional interactions of cancer cells and macrophages - Zaidi, Noorzaileen Eileena; Shazali, Nur Aima Hafiza; Leow, Thean-Chor; Osman, Mohd Azuraidi; Ibrahim, Kamariah; Cheng, Wan-Hee; Lai, Kok-Song; Nik Abd Rahman, Nik Mohd Afizan (MDPI, 2022)
Tumour heterogeneity refers to the complexity of cell subpopulations coexisting within the tumour microenvironment (TME), such as proliferating tumour cells, tumour stromal cells and infiltrating immune cells. The bidirectional interactions between cancer and the surrounding microenvironment mark the tumour survival and promotion functions, which allow the cancer cells to become invasive and initiate the metastatic cascade. Importantly, these interactions have been closely associated with metabolic reprogramming, which can modulate the differentiation and functions of immune cells and thus initiate the antitumour response. The purpose of this report is to review the CD36 receptor, a prominent cell receptor in metabolic activity specifically in fatty acid (FA) uptake, for the metabolic symbiosis of cancer–macrophage. In this review, we provide an update on metabolic communication between tumour cells and macrophages, as well as how the immunometabolism indirectly orchestrates the tumour metastasis.